Bangladesh : Joint Bank-Fund Debt Sustainability Analysis, 2018 Update - International Development Association; International Monetary Fund (World Bank, Washington, DC, 2018)
This debt sustainability analysis (DSA) fully updates the May 2017 joint IMF/WB DSA. Bangladesh’s risks of external debt distress and overall debt distress continue to be assessed as low. The FY17 fiscal deficit remains well below the 5 percent of GDP budget target. Spending control and slower implementation of development projects more than compensated for revenue underperformance. The issuance of National Savings Certificates (NSCs) remains high. Over the medium term, debt ratios are projected to remain on a sustainable path, assuming continued spending restraint, with the deficit used to finance productive investment. Boosting budget revenue is key to creating fiscal space for diversification and growth. The authorities are delaying the implementation of the VAT reform further by two years. Any additional costs from spending pressures ahead of the parliamentary elections and from the Rohingya refugees remain key risks.